Old Age Homes: Vital in Promoting Well-being and Goodwill of Senior Citizens - Dr. Radhika Kapur, (Indian Journal of Social Science and Literature (IJSSL), 2024)
The individuals, belonging to all communities do not feel pleasurable and contented in some cases living with their elderly family members. They consider them as liabilities. They form the viewpoint that these individuals will interfere in their lives, hence, they send them to old age homes. This is unfortunate that when family members do not get along with each other, senior citizens go to old age homes. Within these homes, there are occurrences of various types of amenities and facilities, which are facilitating in leading to up-gradation of overall living conditions of individuals. The individuals, who are employed, are required to be well-versed in terms of their job duties and responsibilities. Furthermore, they are required to be well-equipped in terms of different types of methodologies and procedures, which are facilitating in doing well in one’s tasks and activities. The primary objective of all old age homes is to promote well-being and goodwill of senior citizens. The individuals in old age are overwhelmed by different types of health problems and illnesses, hence, there are provision of medical and health care facilities as well. Furthermore, they are experiencing the psychological problems of anger, stress, anxiety, frustration and depression. For this purpose, they are required to obtain counseling and guidance services. These are facilitating in promoting a normal mind-set and coping with different types of psychological problems in a satisfactory manner. Therefore, old age homes are vital in promoting well-being and goodwill of senior citizens. The main concepts that are taken into account in this research paper are, understanding the meaning and significance of old age homes, factors highlighting the living conditions of individuals in old age homes and experiences of senior citizens in old age homes.